In vitro test of high and low carbon cobalt chromium molybdenum alloys on U937 cell [electronic resource] - Norsamsiah Muhamad @ Wahab, 1982- (2011)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2011